Histological reclassification of parotid gland carcinomas: importance for clinicians - Stodulski, Dominik; Majewska, Hanna; Skálová, Alena; Mikaszewski, Bogusław; Biernat, Wojciech; Stankiewicz, Czesław (European archives of oto-rhino-laryngology, 2016)
Reassessment of histological specimens of salivary gland carcinomas is associated with a change of primary diagnosis in a significant number of patients. The authors evaluated the relation between reclassification/verification of histological diagnosis and the clinical course of parotid gland carcinomas. Histological and immunohistochemical examinations of 111 specimens of parotid gland carcinomas operated on during the years 1992-2010 were revised and in some cases supplemented with cytogenetic tests (FISH), to verify the diagnosis and potentially reclassify the tumours. Analysis of the clinical documentation and follow-up data of patients whose diagnosis was changed was then carried out. The prognostic factors taken into account in the evaluation of the clinical course included the T and N stage, the tumour grade and the extent of resection. The primary diagnosis was changed on review in 28 patients (25.2 %). In 16 patients, the change involved a different histological type of cancer. In six cases, what was thought to be a primary salivary gland cancer was reclassified as a secondary tumour. In four other cases, the change was made from a malignant to a benign tumour and in one case to a non-neoplastic lesion (necrotizing sialometaplasia). Additionally, in two patients with carcinoma ex pleomorphic adenoma, the malignant component was found to be of in situ type. A potentially atypical clinical course was observed in 4 out of 28 patients whose diagnosis was changed. In the case of 2 patients, the course of disease was more aggressive (dissemination, death) than predicted and less aggressive in rest of the patients. Histological reclassification/verification of parotid gland carcinomas can explain the cause of an atypical clinical course in some patients and sometimes enables doctors to implement a change in therapy.
Keywords: Carcinoma; Adenoma, Pleomorphic; Humans; Parotid Neoplasms; lidé středního věku; Clinical course; kohortové studie; Parotid gland carcinoma; Female; Aged; dospělí; senioři; lidé; parotis; Cohort Studies; karcinom; pleomorfní adenom; Adult; Revision; Parotid Gland; staging nádorů; ženské pohlaví; Male; Middle Aged; Histopathology; Neoplasm Staging; mužské pohlaví; nádory příušní žlázy